Primary auditory thalamus relays directly to cortical layer 1 interneurons - Lucas G. Vattino; Christine Junhui Liu; Cathryn P. MacGregor; Carolyn G. Sweeney; Steven Minderler; Anne E. Takesian (iScience, 2025)
Summary: Inhibitory interneurons within cortical layer 1 (L1-INs) integrate inputs from diverse brain regions to modulate sensory processing and plasticity, but the sensory inputs that recruit these interneurons have not been identified. Here, we used monosynaptic retrograde tracing and whole-cell electrophysiology to characterize the thalamic inputs onto two major subpopulations of L1-INs in the mouse auditory cortex. We find that the vast majority of auditory thalamic inputs to these L1-INs unexpectedly arise from the ventral subdivision of the medial geniculate body (MGBv), the tonotopically-organized primary auditory thalamus. Moreover, these interneurons receive robust functional monosynaptic MGBv inputs that are comparable to those recorded in the L4 excitatory pyramidal neurons. Our findings reveal a direct pathway from the primary auditory thalamus to L1-INs, positioning these interneurons to uniquely integrate precise sensory signals with top-down inputs that convey brain states and learned associations.